Efficacy of Ipsilateral, Focal-Simple Limbal Epithelial Transplantation for Large Primary Nasal Pterygia Treatment - Thatte, Shreya; Goyal, Yashas (Journal of Ocular Diseases and Therapeutics, 2021)
Purpose: The long-term success of pterygium surgery is subject to treatment of the limbal stem cell defect. The purpose of this study is to present an alternative method to conjunctival autografting in patients with large pterygia and consequently a large limbal stem cell defect. Methods: 38 Patients with primary nasal pterygium of more than 5 mm limbal involvement were selected for the procedure. Simple limbal epithelial transplantation with human amniotic membrane graft placement over the bare sclera after pterygium excision was done. Patients were followed-up for a period of 12 months. Results: From post-operative day 7, patients had significant improvement in complaints and ocular surface morphology. We reported only one case of graft failure which was a consequence of patient’s non-compliance with post-operative medications and follow-up. Conclusion: Focal-simple limbal epithelial transplantation is an effective alternative to conjunctival limbal autografting in patients with large pterygia where preservation of virgin conjunctiva is prudent for future ocular surgeries.